The Moderation Role of the Audit Committee Quality on the Effect of the Ownership Structure on Intellectual Capital Disclosures (Jurnal Dinamika Akuntansi, 2018)
Intellectual capital is an intangible asset which is able to increase company’s value. Intellectual capital inherent to skill, knowledge and experience that can create competitive advantage for company. The purposes of this study are to analyze the effect of ownership structure (managerial ownership, institutional ownership, government ownership, foreign ownership with the quality of audit committee as moderating variable on intellectual capital. The population of this study is financial companies listed in Indonesia Stock Exchange from 2013 until 2015. Samples are selected using purposive sampling method, and obtained 165 units as observations. Data was collected by documentation, and the analysis data is moderated regression analysis. The study found that managerial ownership has negative effect on intellectual capital disclosure. Government ownership and foreign ownership has positive effect on intellectual capital disclosure, and institutional ownership has not been proven to effect on intellectual capital disclosure. Then, the study also found that the quality of audit committee has significant effect as a moderating variable on the influence of institutional ownership, but it has not been proven to have a moderating effect on the influence of managerial ownership, government ownership and foreign ownership intellectual capital disclosure. The recommendation for further study is to use another technique such as questionnaires that is directly given to company for discovering the level of company’s intellectual capital disclosure. For the company, the limitation of managerial ownership can be used as a control to the company disclosure practice, and improve the role of audit committee to maximize disclosure practice in the company.